Pharmaco-fUS for Characterizing Drugs for Alzheimer’s Disease – The Case of THN201, a Drug Combination of Donepezil Plus Mefloquine - Vidal, Benjamin; Droguerre, Marine; Valdebenito, Marco; Zimmer, Luc; Hamon, Michel; Mouthon, Franck; Charvériat, Mathieu (Frontiers in Neuroscience, 2020)
Donepezil is a potent acetylcholinesterase inhibitor, largely used worldwide to alleviate cognitive symptoms in Alzheimer’s disease (AD). Beyond the widely described neuronal impact of donepezil, it was recently shown that targeting connexins, the proteins involved in astrocyte network organization, potentiates donepezil efficacy profile using behavioral tests in AD rodent models. We herein present data demonstrating the potential of functional ultrasound imaging to monitor cerebral activity changes after pharmacological challenge in mice. As an example, we showed that although administration of donepezil or mefloquine alone at low dose had only very limited effects on the signal compared to the baseline, their combination produced marked hemodynamic effects in the hippocampus, in line with previously published behavioral data demonstrating a synergic interaction between both drugs. Thus, the present study provides new perspectives, (i) through the use of pharmaco-fUS, a new non-clinical imaging modality, to move forward drug discovery in AD and (ii) by the profiling of two drug treatments on brain dynamics, one used in AD: donepezil, and the other in development: donepezil combined with mefloquine (THN201) as a modulator of astrocyte network.